CRYOPRESERVATION OF KAMPUNG ROOSTER SEMEN USING EGG YOLK DILUENT FROM FOUR TYPES OF POULTRY WITH DIFFERENT CONCENTRATIONS - Khairuddin Khairuddin; Muhammad Erik Kurniawan; Soman Soman (Jurnal Kedokteran Hewan, 2019)
The aim of this study was to determine the type and the best concentration of egg yolk in maintaining the quality of kampung rooster spermatozoa during cryopreservation. This study used a completely randomized factorial pattern design with the first factor was the type of egg yolk (purebred chicken, kampung chicken, duck, and quail) and the second factor was the concentration of egg yolk (5%, 10%, and 15%). Semen was collected from twelve kampung roosters using massage method. Immediately after collection, the semen was evaluated macroscopically and microscopically. Semen with more than 70% motility was used in this study. The semen was diluted, packed in a ministraw, equilibrated, and frozen using liquid nitrogen vapor and stored in a liquid nitrogen container for 24 hours. Observation of spermatozoa motility was carried out in fresh semen, diluted semen, after equilibration and after thawing with four replications. The results showed that the type of egg yolk treatment had no effect (P0.05) on the recovery rate and motility of spermatozoa before and after cryopreservation, but egg yolk concentration had a highly significant effect (P0.01) on the quality of spermatozoa. Egg yolks in 10-15% concentration had spermatozoa motility and recovery rate higher than egg yolk with 5% concentration. In conclusion, purebred chicken egg yolk, kampung chicken egg yolk, duck egg yolk, and quail egg yolk each in diluent can be used to maintain the quality of kampung rooster spermatozoa at a concentration of 10-15% during cryopreservation.